Investigation of thermodynamic and surface characterisation of 4-[4-(2-ethylhexyloxy)benzoyloxy] benzoic acid thermotropic liquid crystal by inverse gas chromatography - Cakar, Fatih; Ocak, Hale; Ozturk, Emine; Mutlu-Yanic, Serap; Kaya, Dila; San, Nevim; Cankurtaran, Ozlem; Bilgin-Eran, Belkis; Karaman, Ferdane (TAYLOR & FRANCIS LTD, 2014)
The inverse gas chromatography method was used to obtain thermodynamic and surface properties of the thermotropic liquid crystalline material, 4-[4-(2-ethylhexyloxy) benzoyloxy]benzoic acid (EBBA). The retention diagrams of undecane, dodecane, tridecane, ethyl acetate, n-butyl acetate, iso-butyl acetate, toluene, ethylbenzene, iso-propylbenzene, n-propylbenzene and chlorobenzene on EBBA were plotted at temperatures between 443.2 and 468.2 K. The specific retention volume, V-g(0), Flory-Huggins interaction parameter, chi(infinity)(12), equation-of-state interaction parameter,. chi(*)(12), and effective exchange energy parameter, X-eff, were determined. The dispersive component of the surface free energy, gamma(D)(S), of the studied adsorbent surface was estimated using retention times of different nonpolar organic solvents in the infinite dilution region. The specific free energy of adsorption, Delta G(A)(S), the enthalpy of adsorption, Delta H-A(S), and the entropy of adsorption, Delta S-A(S), of solvents on liquid crystal were determined. The values of Delta H-A(S) were correlated with the donor and the acceptor numbers of the probes to quantify the acidic K-A and the basic K-D parameters of the liquid crystal surface. The values obtained for K-A and K-D parameters indicated an acidic character for the surface of EBBA.
Keywords: liquid crystals; inverse gas chromatography; thermodynamic interaction parameters; surface properties; BEHAVIOR; BASE; DERIVATIVES; ADSORPTION; MOLECULES; NETWORKS; POLYMERS; SYSTEMS; PHASE; Chemistry; Crystallography; Materials Science